Magnetotransport across the metal–graphene hybrid interface and its modulation by gate voltage1. Issue 12 (28th March 2015) - Chen, Jing-Jing; Ke, Xiaoxing; Van Tendeloo, Gustaaf; Meng, Jie; Zhou, Yang-Bo; Liao, Zhi-Min; Yu, Da-Peng
<x xml:space="preserve">Abstract</x> The Au–graphene–Au vertical junction shows a large magnetoresistance and provides a good platform to unveil the graphene interface properties.